1380. Effect of Absolute Body Weight on Clinical Outcomes of Obese Patients Treated with Cefepime. (26th November 2018) - Wagner, Jamie L; Morrison, Austin R; Loper, J Taylor; Barber, Katie E; Stover, Kayla R
Abstract: Background: Differences in pharmacokinetic and pharmacodynamic parameters for obese (OB) patients compared with nonobese (NOB) patients are well known, but drug safety and efficacy when using package insert dosing remain unclear. The purpose of this study was to evaluate the clinical outcomes of cefepime (FEP) for OB patients vs. NOB patients. Methods: This retrospective cohort included inpatient adults ≥18 years treated with FEP monotherapy for ≥72 hours between July 2015 and July 2017. Exclusion criteria were source control not achieved within 72 hours and polymicrobial infections requiring > 1 antibiotic for definitive therapy. Additional data collected were demographics, comorbid conditions, laboratory markers, site of infection, and microbiology. The primary endpoint was clinical treatment failure, defined as change in definitive therapy at >72 hours due to clinical worsening, leukocytosis (WBC > 10 × 10 9 /L) for >72 hours after treatment initiation, fever (single temperature >100.9°F) after >72 hours of treatment initiation, or readmission within 30 days due to re-infection. Secondary outcomes were 30-day inpatient all-cause mortality and 30-day readmission. Results: One hundred fourteen subjects were included (58 OB; 56 NOB). Median (IQR) age 58[46–66] years; 66(58%) males. Median [IQR] weight 107[95–124] kg OB patients; 75[63–84] kg NOB patients. Median Charlson score was 3[2–5] ( P = 0.478). Sixty-two percent OB patients vs. 46% NOB patients experienced a respiratory infection ( P = 0.094); 28% OB patients vs. 39% NOB patients experienced a urinary tract infection ( P = 0.185). 62% OB patients and 59% NOB patients received FEP 1g q8h ( P = 0.732). Most common minimum inhibitory concentration (MIC) in both groups was 1 mg/L (74% OB vs. 83% NOB; P = 0.289). Clinical failure occurred in 52% (67% OB vs. 36% NOB; P = 0.001). OB patients more likely to need a second antibiotic (31% vs. 14%; P = 0.033) and have persistent leukocytosis (50% vs. 30%; P = 0.033). Inpatient all-cause mortality occurred in 17% (22% OB vs. 12% NOB; P = 0.164). 72% of patients were not readmitted within 30 days of discharge. Conclusion: OB patients experienced higher treatment failure than NOB patients. Further examination is needed to assess impact of FEP dose and organism MIC on clinical failure in OB patients. Disclosures: All authors: No reported disclosures.